Load Balancing untuk Lalu Lintas Tinggi pada Lingkungan Cloud Menggunakan Metode Round Robin - Siregar, Dodi; Ariangga, Afrilian; Sarudin, Sarudin; Harahap, Herlina; Liza, Risko (Teknik Informatika Universitas Pamulang, 2024)
The rapid development of technology has changed many aspects of the data communication process, especially in cloud computing. Cloud computing or commonly known as cloud computing is now widely used. With the increase in cloud usage, there is a significant increase in traffic and causes a load imbalance between servers in the cloud environment. To overcome load imbalance on cloud servers, this research proposes the use of load balancing with a round robin method. Load balancing divides traffic equally between servers to prevent overload and system failure. The round robin algorithm ensures fair distribution by sending requests alternately to available servers. Testing shows a significant reduction in error rates when using load balancing. As many as 30 thousand users per second, the error dropped to 42.37%, 50 thousand users per second caused an error of 66.31%, and 100 thousand users per second resulted in an error of 63.08%. This indicates increased system scalability and ability to effectively handle surges in user requests. Overall, implementing load balancing using the round robin method is able to improve system performance in handling high traffic in a cloud environment, maintain stability, and minimize the risk of failure.